Development and psychometric testing of an instrument designed to measure chronic pain in dogs with osteoarthritis - Brown, Dorothy Cimino (2007)
OBJECTIVE: To develop and psychometrically test an owner self-administered questionnaire designed to assess severity and impact of chronic pain in dogs with osteoarthritis. SAMPLE POPULATION: 70 owners of dogs with osteoarthritis and 50 owners of clinically normal dogs. PROCEDURES: Standard methods for the stepwise development and testing of instruments designed to assess subjective states were used. Items were generated through focus groups and an expert panel. Items were tested for readability and ambiguity, and poorly performing items were removed. The reduced set of items was subjected to factor analysis, reliability testing, and validity testing. RESULTS: Severity of pain and interference with function were 2 factors identified and named on the basis of the items contained in them. Cronbach’s α was 0.93 and 0.89, respectively, suggesting that the items in each factor could be assessed as a group to compute factor scores (ie, severity score and interference score). The test-retest analysis revealed κ values of 0.75 for the severity score and 0.81 for the interference score. Scores correlated moderately well (r = 0.51 and 0.50, respectively) with the overall quality-of-life (QOL) question, such that as severity and interference scores increased, QOL decreased. Clinically normal dogs had significantly lower severity and interference scores than dogs with osteoarthritis. CONCLUSIONS AND CLINICAL RELEVANCE: A psychometrically sound instrument was developed. Responsiveness testing must be conducted to determine whether the questionnaire will be useful in reliably obtaining quantifiable assessments from owners regarding the severity and impact of chronic pain and its treatment on dogs with osteoarthritis.